2016
DOI: 10.5453/jhps.51.51
|View full text |Cite
|
Sign up to set email alerts
|

<sup>137</sup>Cs Environmental Half-life without Remediation: Impact on Radiation Dose

Abstract: Cs is an important long-term contributor to radiation dose and risk following a nuclear accident. Its high abundance (about Fukushima accident. After this event, extensive amounts of time and money were invested to clean-up and limit the transport of 137 Cs into the food chain. However, since the biological and environmental half-lives of 137 Cs are short, they limit its availability and exposure in people. This paper demonstrates how historical data on the environmental half-life of 137 Cs in both 137 Cs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, during transport through the environment, there are several processes that limit pathways for movement of the radionuclide from the environment to people. These processes result in a rapid decrease in biological availability or the environmental half-life, which with time after deposition limits the uptake of 137 Cs into the food chain (Brooks et al 2016). These processes are important in long-term storage of 137 Cs, since accidental release into the environment can be modified by natural processes that make it less readily available for human uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during transport through the environment, there are several processes that limit pathways for movement of the radionuclide from the environment to people. These processes result in a rapid decrease in biological availability or the environmental half-life, which with time after deposition limits the uptake of 137 Cs into the food chain (Brooks et al 2016). These processes are important in long-term storage of 137 Cs, since accidental release into the environment can be modified by natural processes that make it less readily available for human uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Since 137 Cs binds strongly with clay particles in the soil, it has a short environmental half-life (the time from deposition until it can be incorporated into the biosphere). Thus, it rapidly becomes more biologically unavailable as a function of time (Brooks et al 2016), so that even without environmental remediation, the potential for internal deposition decreases rapidly with time. Under most environmental conditions without a continued source of the radionuclide to facilitate uptake into the body, the gamma shine and external dose from 137 Cs in soil is the major human health hazard.…”
Section: Cesium ( 137 Cs)mentioning
confidence: 99%
“…In previous research, it has been shown that Cs 137 indeed accumulates more in organs like the gastrointestinal tract and liver when fed orally to mice (Nelson et al 1961) and in gastrointestinal tract, heart, kidney and liver when injected to dogs (Leggett et al 2003), implying that metabolically active organs gain higher doses of Cs 137 . In addition, Cs 137 has been shown to increase concentration in higher stages of the food chain and its biological half-life often increases with the body mass (Pendleton et al 1965;Brooks et al 2016). Doses used in many previous radiation studies testing organs have been high and acute (e.g.…”
Section: Introductionmentioning
confidence: 99%